Penguatan Moderasi Beragama dengan Pendekatan Dakwah Digital pada Pemuda Pelopor Kota Payakumbuh (P2KP) - Roza, Yanti Mulia; Yoliadi, Dodi Nofri; Hidayat, Wahyu (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This community service program discusses strengthening religious moderation in the Payakumbuh City Pioneer Youth (P2KP) community through a digital preaching approach. This activity aims to improve youth understanding of the concept of religious moderation and their technical skills in preaching through digital platforms. As agents of change, Payakumbuh City Pioneer Youth are expected to be examples of tolerance and peace in society by implementing digital methods in delivering moderate religious messages. The method used in this program is Asset-Based Community Development (ABCD), which involves five stages: discovery, dream, design, define, and destiny. Each stage is focused on exploring potential and overcoming internal and external challenges faced by this community in spreading religious moderation-based preaching. This program is implemented with support from various parties, including the Payakumbuh City Interfaith Harmony Forum (FKUB), and uses various social media as a preaching tool. The results of the activity show an increase in understanding of religious moderation and an increase in technical skills in creating digital content. With this program, it is hoped that the younger generation can play an active role in creating a more inclusive society that respects diversity.